Development of the UNOChem Game to Improve Students Critical Thinking Skills on Factors that Affect the Reaction Rate Topic - Hidayah, Putya; Rusmini, Rusmini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The UNOChem game is a development of the UNO Stacko game that has been modified and designed with chemistry materials. This research aims to develop UNOChem games to improve students' critical thinking skills on the material factors that affect the appropriate reaction rate. The feasibility of the UNOChem game is seen in its validity, practicality, and effectiveness. This research refers to 4D design with three stages: define, design, and development. The limited trial was carried out in class XI-2 of SMAN 1 Kedamean. The indicators used in this study are interpretation, analysis, and inference. The validity was obtained from the results of the game assessment by two chemistry lecturers and one chemistry teacher. Practicality was obtained from observation of student activities and a questionnaire of student responses after using the UNOChem game. Effectiveness was obtained from the student's critical thinking skills test results. The study results showed that the validity obtained in each aspect of the obtaining mode was ≥ 4. The practicality of the UNOChem game based on the results of observation of students' activities as a whole got a practicality percentage of 87.4%. Meanwhile, based on the student response questionnaire, in the aspect of describing the level of students' interest in the UNOChem game, the percentage of practicality was 100%; in the aspect of describing the level of ease of understanding the material and doing critical thinking problems in understanding the material, the percentage of practicality was 93.3%. In describing the ease of using the game in the game, the rate of practicality was 94.9%. The game's effectiveness was obtained through an n-gain test with a score of 0.72. The effectiveness of the media is supported by the Wilcoxon Signed Rank Test (a non-parametric test), which shows a Sig. A value of 0.000 means there is a significant difference, and the UNOChem game can be declared effective. Based on the research results, the UNOChem game is suitable for learning material activities related to factors that affect the reaction rate of class XI high school.